Unilateral sudden hearing loss as the first presenting symptom of chronic myeloid leukemia: a case report and literature review - Sun, Le; Yin, Yue; Guo, Xiang; Yu, Fan; Xu, Jinkun (Frontiers in Oncology, 2025)
Chronic myeloid leukemia (CML) with sudden deafness as the first symptom is clinically rare and easily overlooked. No conventional treatment for CML-associated sudden hearing loss exists and hearing outcomes remain poor. Here, we describe a case in which sudden unilateral hearing loss was the first presenting symptom in a patient ultimately diagnosed with CML. The patient received imatinib mesylate, sodium bicarbonate, and allopurinol for CML, and systemic and local steroids, hemoreological therapy, and nutritional neurological drugs for hearing loss. Although the patient’s CML was effectively controlled, his hearing could not be restored. In the second part of the manuscript, we present the results of a systematic review of case reports of CML-associated sudden hearing loss, identified by screening PubMed, Web of Science, and Medline. Seventeen patients were identified. Hyperviscosity syndrome and labyrinthine artery occlusive infarction were the most common pathogenic mechanisms of hearing loss. In terms of auditory outcomes, eight patients showed no improvement, while nine demonstrated positive outcomes. Among those with improved hearing, four had undergone cochlear implantation, one received intrathecal methotrexate, and one underwent leukoreduction therapy. Aggressive cochlear implantation could improve hearing outcomes in cases where cochlear ossification has not taken place and the leukemia is controlled.